1995
DOI: 10.1073/pnas.92.7.3032
|View full text |Cite
|
Sign up to set email alerts
|

Inflammatory processes induce beta-amyloid precursor protein changes in mouse brain.

Abstract: In Alzheimer disease, a combination of genetic predisposition and environmental factors may contribute to changes in j8-amyloid precursor protein (APP) expression, f3-amyloid peptide deposition, and neuronal loss. Factors such as head injury or acute infection that trigger inflammatory processes may play a crucial role in development of the disease. In the present in vivo study, we showed that, in mouse brain, peripheral stimulation with lipopolysaccharide (LPS) induced a transient increase in the inflammat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

10
95
0

Year Published

1999
1999
2016
2016

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 181 publications
(105 citation statements)
references
References 43 publications
10
95
0
Order By: Relevance
“…Systemic administration of LPS to rodents causes upregulation of COX2 in brain perivascular and endothelial cells (Elmquist et al, 1997;Yermakova and O'Banion, 2001) and alters the expression or processing of APP or both. It also accelerates the generation of Aβ42 in transgenic mice that overexpress the Swedish variant of APP695 (Sheng et al, 2003) and increases the abundance of APP751 (Brugg et al, 1995). LPS could cause these effects by several mechanisms.…”
Section: Discussionmentioning
confidence: 99%
“…Systemic administration of LPS to rodents causes upregulation of COX2 in brain perivascular and endothelial cells (Elmquist et al, 1997;Yermakova and O'Banion, 2001) and alters the expression or processing of APP or both. It also accelerates the generation of Aβ42 in transgenic mice that overexpress the Swedish variant of APP695 (Sheng et al, 2003) and increases the abundance of APP751 (Brugg et al, 1995). LPS could cause these effects by several mechanisms.…”
Section: Discussionmentioning
confidence: 99%
“…It has been shown previously that peripheral stimulation with LPS induced a transient increase in inflammatory cytokine mRNAs, and changes in APP isoforms in the brains of mice [6]. In addition, others have shown that bacterial LPS infused into the rat brain induces an inflammatory response as indicated by microglial reactivity and cytokine expression, characteristic of inflammation in the AD brain [14].…”
Section: Amyloid Depositionmentioning
confidence: 93%
“…Stimuli that lead to microglial priming, such as systemic infections and elevated plasma IL-1β/TNF-α, are correlated with accelerated cognitive decline in Alzheimer's disease patients (1,2). In Alzheimer's disease models, repeated LPS challenges exacerbate tau pathology (3), inflammation (4), and amyloid deposition (5). In prion disease models, microglial priming is evident even in the preclinical stage, and LPS challenge exacerbates neuronal death, induces acute cognitive impairment, and accelerates disease progression (6)(7)(8).…”
mentioning
confidence: 99%